Overexpression of an Arabidopsis Formin Stimulates Supernumerary Actin Cable Formation from Pollen Tube Cell Membrane - Cheung, Alice Y. (American Society of Plant Biologists, 2004)
Formins, actin-nucleating proteins that stimulate the de novo polymerization of actin filaments, are important for diverse cellular and developmental processes, especially those dependent on polarity establishment. A subset of plant formins, referred to as group I, is distinct from formins from other species in having evolved a unique N-terminal structure with a signal peptide, a Pro-rich, potentially glycosylated extracellular domain, and a transmembrane domain. We show here that overexpression of the Arabidopsis formin AFH1 in pollen tubes induces the formation of arrays of actin cables that project into the cytoplasm from the cell membrane and that its N-terminal structure targets AFH1 to the cell membrane. Pollen tube elongation is a polar cell growth process dependent on an active and tightly regulated actin cytoskeleton. Slight increases in AFH1 stimulate growth, but its overexpression induces tube broadening, growth depolarization, and growth arrest in transformed pollen tubes. These results suggest that AFH1-regulated actin polymerization is important for the polar pollen cell growth process. Moreover, severe membrane deformation was observed in the apical region of tip-expanded, AFH1-overexpressing pollen tubes in which an abundance of AFH1-induced membrane-associated actin cables was evident. These observations suggest that regulated AFH1 activity at the cell surface is important for maintaining tip-focused cell membrane expansion for the polar extension of pollen tubes. The cell surface–located group-I formins may play the integrin-analogous role as mediators of external stimuli to the actin cytoskeleton, and AFH1 could be important for mediating extracellular signals from female tissues to elicit the proper pollen tube growth response during pollination.